USAHA MENGATASI HYSTERIA DAN NEURASTHENIA MELALUI PENDIDIKAN DIRI SENDIRI - Hasibuan, Muslim (Darul Ilmi: Jurnal Ilmu Kependidikan dan Keislaman, 2013)
This paper puts forward about psychiatric disorders (Neurosis) whichÂ  focuses on hysteria and neurasthenia. Hysteria is caused by the inability of a person to face difficulty, arising restlessness, anxiety and other mental conflict, and lack of ability to adjust to real life, because conflict soul in his life in the past and the present. Neurasthenia is a crummy disease, the patient's whole body is felt tired, no spirit, easy to feel crummy, and sometimes quick-tempered, not able to continue to think about something problems, difficulty concentrating, and difficulty remembering, feeling apathetic and indifferent, difficulty sleeping, the head is always dizzy sometimes head was going to burst, he is feeling sick and is always afraid of dying. To solve and avoid you from psychiatric disorders (hysteria and neurasthenia) is the self-Â  education, in this case the ability of a person to know himself, and to know and appreciate who the Lord (the Most Acting, All-Knowing, All-Merciful, All-Knowing, and the most of everything). So, he always remembers Him (Asma-name of Allah) that comes from his heart.